A pedagogia das competências nas práticas pedagógicas dos professores nas escolas estaduais de educação tecnológica do estado do Pará - RODRIGUES, Jaqueline do Nascimento (Universidade Federal do Pará, 2013)
Treats this dissertation of the teacher's pedagogic practices in Para's State Schools of Technological Education, that adhered the Pedagogy of the Competences. The field research had as general objective to identify and to analyze what stays of the Pedagogy of the Competences in the teacher's practices in the Technological Schools. For this it characterized sententiously the pedagogic practices proposed by the Pedagogy of the Competences; identified the teacher's pedagogic practices of three Schools Technological of Pará that tried to implement the reform of the technical teaching of the years 1990 and, finally, it analyzed the pedagogic strategies in use for the professionals of the education looking for to identify ruptures and continuities, in the educational practices, between these and the recommendations originating from Pedagogy of the Competences. To reach these objectives and to reveal the problem proposal, it was contributed in the theoretical-methodological referential materialism of the historical-dialectical. Preceded from bibliographical revision the field research was accomplished making use of interviews structure forms and support observations. The analysis of data was accomplished through the content analysis. The accomplished research indicates as found that the pedagogic practices of teachers that adhered to the Pedagogy of the Competences and that tried to implement assumed the market as main reference, values the active methods as methodological strategy, quest to articulate instrumental theory and practice and that it is not executed by participant mode.